A case for feedback and monitoring assessment in competency‐based medical education. Issue 4 (18th December 2019) - Egan, Rylan; Chaplin, Timothy; Szulewski, Adam; Braund, Heather; Cofie, Nicholas; McColl, Tamara; Hall, Andrew K.; Dagnone, Damon; Kelley, Leah; Thoma, Brent
Abstract: Purpose: Within competency‐based medical education, self‐regulated learning (SRL) requires residents to leverage self‐assessment and faculty feedback. We sought to investigate the potential for competency‐based assessments to foster SRL by quantifying the relationship between faculty feedback and entrustment ratings as well as the congruence between faculty assessment and resident self‐assessment. Materials and methods: We collected comments in (a) an emergency medicine objective structured clinical examination group (objective structured clinical examinations [OSCE] and emergency medicine OSCE group [EMOG]) and (b) a first‐year resident multidisciplinary resuscitation "Nightmares" course assessment group (NCAG) and OSCE group (NOG). We assessed comments across five domains including Initial Assessment (IA), Diagnostic Action (DA), Therapeutic Action (TA), Communication (COM), and entrustment. Analyses included structured qualitative coding and (non)parametric and descriptive analyses. Results: In the EMOG, faculty's positive comments in the entrustment domain corresponded to lower entrustment score Mean Ranks (MRs) for IA (<11.1), DA (<11.2), and entrustment (<11.6). In NOG, faculty's negative comments resulted in lower entrustment score MRs for TA (<11.8 and <10) and DA (<12.4), and positive comments resulted in higher entrustment score MRs for IA (>15.4) and COM (>17.6). In the NCAG, faculty's positive IA comments were negatively correlated with entrustment scores ( ρ = −.27, P = .04). Across programs, faculty and residents made similar domain‐specific comments 13% of the time. Conclusions: Minimal and inconsistent associations were found between narrative and numerical feedback. Performance monitoring accuracy and feedback should be included in assessment validation.